Repetitive Sequence Stability in Embryonic Stem Cells - Shi, Guang; Pang, Qianwen; Lin, Zhancheng; Zhang, Xinyi; Huang, Kaimeng (International journal of molecular sciences, 2024)
Repetitive sequences play an indispensable role in gene expression, transcriptional regulation, and chromosome arrangements through trans and cis regulation. In this review, focusing on recent advances, we summarize the epigenetic regulatory mechanisms of repetitive sequences in embryonic stem cells. We aim to bridge the knowledge gap by discussing DNA damage repair pathway choices on repetitive sequences and summarizing the significance of chromatin organization on repetitive sequences in response to DNA damage. By consolidating these insights, we underscore the critical relationship between the stability of repetitive sequences and early embryonic development, seeking to provide a deeper understanding of repetitive sequence stability and setting the stage for further research and potential therapeutic strategies in developmental biology and regenerative medicine.